Improving the abilty of problem solving and independence of mathematical vocational school through contextual approaches - abdul wahab abdulah; Asep Subhan Suryadi (IKIP Siliwangi, 2019)
The background of this research is to know the needs of learning approach to deal with the ability of student in vocational high school to solve problems and their mathematic independent. The alternative approach applied is contextual approach. This research purpose is to find out the achievement and the increase of their ability in solving problems and their mathematic independent. Research methodology used in this research is experiment method. In the beginning and in the end of learning both of the class given test and non-test. Population of this research is vocational students which has intermediate skill in Bandung Barat residence, sample taken from two class randomly, the sample is X TKJ 2 as experiment class and X TKJ 3 class as control class. Instrument of the research is a test consist of 8 essay questions and 30 non-test questions. The solving problems ability and math independent then analyze using average differential test. The result of the research shows that the achievement and the ability of solving problems and math independent increasing using contextual approach than conventional approach